Possible role of acetylcholine in regulating spatial novelty effects on theta rhythm and grid cells - Barry, Caswell; Heys, James G.; Hasselmo, Michael E. (Frontiers in Neural Circuits, 2012)
Pharmacological and lesion data indicate that acetylcholine plays an important role in memory formation. Increased levels of acetylcholine in the hippocampal formation are associated with successful encoding while disruption of the cholinergic system leads to impairments on a range of mnemonic tasks. Cholinergic signalling from the medial septum also plays a central role in generating and pacing theta-band oscillations throughout the hippocampal formation. New results suggest a potential link between these distinct phenomena. Environmental novelty, a condition associated with strong cholinergic drive, has been shown to induce an expansion in the firing pattern of entorhinal grid cells and a reduction in the frequency of theta measured from the LFP. Computational modelling suggests the spatial activity of grid cells is produced by interference between neuronal oscillators; scale being determined by theta-band oscillations in entorhinal stellate cells, the frequency of which are modulated by acetylcholine. We propose a causal link: increased cholinergic signalling in response to environmental novelty triggers grid expansion. Cholinergic induced grid expansion may enhance, or even induce, encoding by producing a mismatch between spatial inputs to the hippocampus, such as barrier cells and grids cell with different scales.